Alaska on the Go : Exploring the 49th State with Children - Kirkland, Erin (Book collections on Project MUSE., 2014)
Nearly two million people visit Alaska every year, drawn to its spectacular views and endless activities. But with such size and so many options, it can seem overwhelming when it comes to planning a family vacation to the 49th state. The best place to start? With a local, of course. Journalist and Alaska resident Erin Kirkland knows every corner of the state, and she has crossed thousands of miles with her son. In Alaska on the Go, she offers a fresh take on exploring some of the most beautiful land in the world, with tips and tricks that only an insider knows. Serving as the perfect tour guide.